Functional Hemispheric Specialization in Processing Phonemic and Prosodic Auditory Changes in Neonates - Arimitsu, Takeshi; Uchida-Ota, Mariko; Yagihashi, Tatsuhiko; Kojima, Shozo; Watanabe, Shigeru; Hokuto, Isamu; Ikeda, Kazushige; Takahashi, Takao; Minagawa-Kawai, Yasuyo (Frontiers in Psychology, 2011)
This study focuses on the early cerebral base of speech perception by examining functional lateralization in neonates for processing segmental and suprasegmental features of speech. For this purpose, auditory evoked responses of full-term neonates to phonemic and prosodic contrasts were measured in their temporal area and part of the frontal and parietal areas using near-infrared spectroscopy (NIRS). Stimuli used here were phonemic contrast /itta/ and /itte/ and prosodic contrast of declarative and interrogative forms /itta/ and /itta?/. The results showed clear hemodynamic responses to both phonemic and prosodic changes in the temporal areas and part of the parietal and frontal regions. In particular, significantly higher hemoglobin (Hb) changes were observed for the prosodic change in the right temporal area than for that in the left one, whereas Hb responses to the vowel change were similarly elicited in bilateral temporal areas. However, Hb responses to the vowel contrast were asymmetrical in the parietal area (around supra marginal gyrus), with stronger activation in the left. These results suggest a specialized function of the right hemisphere in prosody processing, which is already present in neonates. The parietal activities during phonemic processing were discussed in relation to verbal-auditory short-term memory. On the basis of this study and previous studies on older infants, the developmental process of functional lateralization from birth to 2 years of age for vowel and prosody was summarized.